Stratigraphy and facies architecture of the uppermost fan system in the Tanqua sub-basin, Permian Ecca Group, South Africa - Van der Merwe, Willem C (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2005.